Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 10 No 1 (2024): NIU Journal of Social Sciences, Vol. 10 No. 1, March 2024, 2024)
This edition of KIU Journal of Social Sciences focuses on Development Administration, Educational Psychology, Social Philosophy, Business and Entrepreneurial Studies as well as Creative Studies. The first part of the Journal addresses issues in Development Administration such as Commercial Agriculture, Revenue or Fiscal Policies, Debt Management, Imperialism, Welfare Services, Rural Development and Good Governanace. It is argued in one of the papers that monetary policy fundamentals have significant push-up effects on commodity prices. It is therefore, suggested amongst others, that the monetary policy authority should attractively peg the price of government’s securities, moderate money supply and interest rate to enhance monetary stability for driving diversified private sector investments which if sustained will dampen commodity price in the long-run. Papers in the second section are on Educational Psychology. One of the papers in this Section argues that computer assisted instruction method is an effective method for improving students’ Mathematics achievement in students. It is therefore, recommended that recommended that Computer Assisted Instruction should be applied in the teaching of Mathematics in schools to improve academic achievements. Using Nigeria as a case study, one the papers, in the third section on Social Philosophy, examine the problem of corruption in Africa, holistic definition of corruption, nature and characteristics of corruption, evil of corruption, and the causes of corruption, legal and institutional fight against corruption in Nigeria, how religion aids corruption and the role of religion in combating corruption as a social responsibility/intervention in Nigeria. It consequently, recommends that religious institution should as a matter of urgency be the watchdog and the conscience of the common man in nation with respect to combating corruption in Nigeria. Papers in the fourth section are on Business and Entrepreneurial Studies. It is revealed in one of the papers in this section that corporate entrepreneurship dimensions correlated significantly with performance of selected deposit money banks in Nigeria. The paper therefore, recommends that value creation of top management should indulge the opinion of their customers through questionnaires and feedback mechanism. This would give the organisation an insight to what the customers’ expectations regarding new things that are brawling up in similar competitive organisations. In the same vein indulging customer’s opinion while launching new products, would make them feel carried along and valuable. In last section on Creative Studies, one of the papers explores how mass media discuss contemporary issues of insecurity. Using Content Analysis Research, the study revealed that bandit attacks and Government security agencies' efforts were the dominant issues, and conflict and human-interest frames were the prominent news frames used to present banditry issues across the three selected television stations. Consequently, findings of the research work support tenets of agenda-setting and framing theories. It is recommended that television stations increase the patterns and depth of their coverage, as well as the news frames used to present banditry issues. On the whole, this issue of KIU Journal of Social Sciences features many interesting research papers. Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors.